2019
DOI: 10.3348/kjr.2018.0409
|View full text |Cite
|
Sign up to set email alerts
|

Solitary Nodular Invasive Mucinous Adenocarcinoma of the Lung: Imaging Diagnosis Using the Morphologic-Metabolic Dissociation Sign

Abstract: Objective To evaluate the efficacy of the morphologic-metabolic (M-M) dissociation sign based on computed tomography (CT) and fluorine-18-fluorodeoxyglucose positron emission tomography (PET)/CT in discriminating invasive mucinous adenocarcinoma (IMA) from invasive non-mucinous adenocarcinomas (ADCs) of the lung. Materials and Methods The Institutional Review Board approved this retrospective study. Among surgically resected solitary pulmonary nodule (SPN)-type ADCs (< … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Typical CT findings of IMA include multiple consolidations or ground-glass opacities mimicking pneumonia; however, there are some reports that a solitary nodule pattern is much more common than pneumonia pattern [ 2 , 6 ]. Pathological features of IMA are characterized by goblet or columnar tumor cells containing abundant cytoplasmic mucin, and a lepidic growth pattern with microscopic skip lesions [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Typical CT findings of IMA include multiple consolidations or ground-glass opacities mimicking pneumonia; however, there are some reports that a solitary nodule pattern is much more common than pneumonia pattern [ 2 , 6 ]. Pathological features of IMA are characterized by goblet or columnar tumor cells containing abundant cytoplasmic mucin, and a lepidic growth pattern with microscopic skip lesions [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Solitary nodular IMA has been reported to be prone to cavitary lung lesions (air bronchogram or vacuolar signs). 16 , 17 The pathological causes of these signs include: 1. Expulsion of mucus from mucus pools through the attached bronchi.…”
Section: Discussionmentioning
confidence: 99%
“…Some reports (17,18) found that the CT value of lung cancer at the level of 40-70 Kev was higher than that of the tuberculosis group in the quantitative analysis of peripheral lung cancer and tuberculoma by energy spectrum. There were many reports on PET/ CT for PPMA (19,20), but there were no reports about CT features of PNMA and tuberculoma. In this study, we found that the CT value of tuberculoma on plain scan was 35.15±16.00, and the CT value of PNMA was 24.00±12.67.…”
Section: Discussionmentioning
confidence: 99%